Determination of Perfluoroalkyl Substances in Municipal Landfill Leachates from Beijing, China - Zhang, Chunhui; Peng, Yi; Niu, Xiameng; Ning, Ke (Asian Journal of Chemistry, 2014)
Perfluoroalkyl substances (PFASs) that accumulate in landfills are a potential source of PFASs via leaching into the surface or groundwater environment. In the study, 10 PFASs, including PFHxA, PFHxS, PFHpA, PFOA, PFNA, PFDA, PFUnDA, PFDoDA, PFTrDA and PFOS were determined in untreated and treated landfill leachates at three landfill sites in Beijing, China. The results showed that PFHxA, PFHpA, PFOA and PFOS were detected in untreated leachates of three landfill sites. The PFASs in treated leachates depended on the different treatment systems. In the full scale treatment, after the biological treatment and reverse osmosis processing, the leachate showed the lowest concentrations and highest removal efficiencies of PFHxA, PFHpA, PFOA and PFOS, followed by landfill leachate after the treatment using biological treatment, microfiltration and activated carbon. The leachate only treated by biological treatment had the highest concentrations and lowest removal efficiencies of PFASs. The ratio of PFHxA, PFHpA and PFOA concentration of leachate to Beijing tap water was 53.4, 4.5 and 132, respectively. The results indicate that municipal landfill leachate is the potential source pollution of PFASs.